2019
DOI: 10.1177/0194599819835545
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Delay in Head and Neck Free Flap Surgery: Risk Factors and Strategies to Minimize Hospital Days

Abstract: Objective Length of stay (LOS) includes time medically necessary in the hospital and time waiting for discharge (DC) afterward. This DC delay is determined in head and neck free flap patients. Reasons for and factors leading to DC delay, as well as associated adverse outcomes, are elucidated. Methods Retrospective chart review was performed for all head and neck free flap surgeries from 2012 to 2017. Data including demographics, comorbidities, and perioperative factors were collected. Regression analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…In their study, Medicaid/self-pay patients had a 4.4-fold higher risk for discharge delay, experiencing a mean 2.8 days of delay. 11 Similarly, our study found that insurance type was significantly associated with increased odds of extended LOS, even after controlling for illness severity, suggesting that attention should be focused on hospital practice differences. Quality improvement projects have demonstrated that these disparities can be improved.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…In their study, Medicaid/self-pay patients had a 4.4-fold higher risk for discharge delay, experiencing a mean 2.8 days of delay. 11 Similarly, our study found that insurance type was significantly associated with increased odds of extended LOS, even after controlling for illness severity, suggesting that attention should be focused on hospital practice differences. Quality improvement projects have demonstrated that these disparities can be improved.…”
Section: Discussionsupporting
confidence: 52%
“…[27][28][29] Additional unnecessary days spent in the hospital are associated with higher rates of hospital-acquired infections, morbidity, and mortality. 11,30 Extended LOS has also been suggested as a contributor to delays in the interval from surgery to initiation of postoperative radiation therapy (S-PORT). 31 Timeliness of care impacts survival outcomes in head and neck cancer, but a majority (55.7%) of patients failed to achieve the recommended S-PORT interval of 6 weeks, and patients with Medicaid were disproportionately affected by these delays.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations